Canales de Distribución con Orientación hacia el mercado. CASO DE LOS MEDICAMENTOS EN LA CIUDAD DE MEDELLÍN, 2001 (2019)
This article summarizes part of the research proyect "Decision Making Criteria About the Nature of the Distribution Channels, from the Manufacturer's Perspective, in Medellín,2001 (Pharmaceutical products)" (Baby, 2001). The article focuses on the channels of distribution in the pharmaceutical consumer market in Medellín. An illustration of the implementation of some steps of a procedure or approach to design or review the nature of the distribution channels of the firm, is presented. The procedure assumes market requirements to be one of the driving forces shaping the decisions made by firms, regarding channels of distribution. Thus, buying behavior and service requirements of final consumers, retailers and wholesalers are shown. The article also shows how to carry out basic analysis leading to the design of marketing strategies and actions directed to the three groups that were investigated.